Theories of educational management and leadership: A review - Ghasemy, Majid; Hussin, Sufean (2014)
Education is the main change agent in developing and developed societies. As a result, the management of educational organizations is regarded as one of the most important management perspectives. Basically, educational management is a discipline with respect to the management of educational organizations and since this field of study has been developed on the premises of other resolutely established disciplines, there is not a unique statement to set out this subject of study. Although the process of determining organizational goals is fundamental to educational management, linking between goals and aims of education and actions of educational management may be considered as vital. The other issue of importance is the closely interlocked relation between educational management and educational leadership and a true combination of them to reach educational excellence. This paper aims to review the models of educational management and their links with the leadership styles based on the discussions as well as the typology of educational management and leadership models provided in the 4th edition of the book “Theories of Educational Management & Leadership” (Bush, 2011).